The philosophy of John Henry Newman and pragmatism : a comparison - Corona, Marial (The Catholic University of America Press, 2023)
"This work places the philosophical insights of John Henry Newman in conversation with philosophers from the pragmatic tradition, particularly with C. S. Peirce, the classical pragmatists, and those who have followed their line, and shows several lines of concurrence. Without claiming that Newman is a pragmatist philosopher, pragmatism is used as a foil, or point of access, to delve into Newman's philosophy and bring forth the richness of his thought while placing him in the canon of philosophy"--